The effect of educational programs on parents’ knowledge, behavior, and practices regarding aluminum phosphide poisoning and its first-aid measures - Mabrouka Attia Ali Nada; Ahmed Kamal Eldin Elsayed Elfeky; Hamida Ahmed Mustafa Darweesh; Farida Khalil Ibrahim Mohamed; Loujain Saud Sharif; Faten Shawky Kandil; Fatma Ahmed Elsobky; Samah Abdallah Mohamed Amer (BMC Pediatrics)
Abstract Background Aluminum phosphide is an excellent insecticide available as a chalky white or brown tablet. Aluminum phosphide is traded in the Egyptian market as tablets under the brand name celphos. To date, no specific antidotes for aluminum phosphide poisoning have been identified. Management is primarily supportive, to control toxic symptoms and prevent the anticipated consequences. Therefore, educating parents about first aid management is of utmost importance. This study aimed to evaluate the knowledge, behavior, and practices of parents concerning aluminum phosphide poisoning and its first-aid measures. Methods This study used a quasi-experimental research design and was conducted in the inpatient clinical toxicology department ward of Menoufia University Hospital between June 2022 and May 2023. Children (n = 98) who met the inclusion criteria (aged between 0 and 18 years and who experienced accidental or suicidal aluminum phosphide poisoning) were recruited from the inpatient clinical toxicology department ward, intensive care unit in the emergency department, and critical care unit of Menoufia University Hospital. Four questionnaires were used to collect data for this study: (1) sociodemographics, poisoning data, physical examination, and laboratory investigations; (2) knowledge of parents; (3) practice of parents; and (4) behavior response scales. Results This study analyzed 98 cases of acute ALP poisoning, predominantly affecting females (67.3%) aged 16–18 years, with most incidents occurring in summer (51.1%) and rural areas (80.6%). Suicidal ingestion accounted for 86.7% of cases, and delays in hospital arrival were noted in 65.3%. Clinical findings included vomiting (76.6%), dyspnea (77.5%), and cardiogenic shock (84.8%). ECG abnormalities were found in 82.7% of patients, and metabolic acidosis was present in 82.3% of patients. An educational program significantly improved the knowledge and first-aid practices of the participants regarding ALP poisoning, highlighting the need for enhanced awareness and intervention strategies. Conclusions Community awareness programs, such as first-aid education initiatives, can positively influence the knowledge, practices, and behaviors of mothers in terms of providing first aid for aluminum phosphide toxicity.